Sosialisasi Pencegahan Penggunaan Vape Sejak Dini pada Siswa Kelas V MI Perwanida Kota Blitar - Lu'lu'ul Jannah; Anggrya Isnani Maheasty; Rizqi Rahmadhani Saputri; Nabila Yumna Sugeng (Kerigan: Jurnal Pengabdian Masyarakat, 2023)
Purpose: This qualitative study aimed to investigate the effectiveness of early prevention strategies for vape use among fifth-grade students at MI Perwanida Elementary School in Blitar. The significance of this research lies in addressing the growing concern of vape use among young children, which can have long-term health and social implications. Method: The study employed a qualitative research design, combining observation, interviews, and documentation. Data was collected through participant observation, semi-structured interviews with students and teachers, and documentation of school policies and programs Practical Applications: The findings of this study can inform the development of evidence-based prevention programs for vape use among elementary school students. By understanding the factors contributing to vape use and the effectiveness of prevention strategies, educators and policymakers can create targeted interventions to mitigate the risks associated with vape use. Conclusion: The study highlights the importance of early prevention and intervention strategies to address vape use among elementary school students. The findings emphasize the need for comprehensive and culturally sensitive programs that engage students, teachers, and parents in addressing this critical issue.